Knowledge center model by incorporating knowledge center features in sharepoint for Malaysian Nuclear Agency - Hassannuddin, Ily Amirah (2014)
This study is to identify and define more clearly what it is the Knowledge Center. An organization of the Malaysian Nuclear Agency has been selected to be the domain of the study. As a knowledge center that includes knowledge management, so this study chose to use SharePoint Malaysian Nuclear Agency as a platform to implement the findings of this knowledge center. Studies of the problems of the current system are identified through interviews with users of the current system in which the problem is not widespread consumerism and misleading. Reviews from previous studies have been done to choose the appropriate knowledge center for SharePoint Malaysian Nuclear Agency. Methodology by Stijn Hoorens, Lidia Villalba van Dijk, and Christian van Stolk was chosen because it contains the exploration phase of the current issues, the specification of the characteristics of the selected knowledge center, analysis and synthesis of the features found and evaluating these features. The specified KC features and KC components were mapped with the SharePoint menu. The main evaluation results where SharePoint Nuclear Malaysia to meet the essential features that are in KC and further assessment is done to identify the characteristics of a deeper KC should have improved in SharePoint.